Low-Light Anoxygenic Photosynthesis and Fe-S-Biogeochemistry in a Microbial Mat - Haas, Sebastian; de Beer, Dirk; Klatt, Judith M.; Fink, Artur; Rench, Rebecca McCauley; Hamilton, Trinity L.; Meyer, Volker; Kakuk, Brian; Macalady, Jennifer L. (Frontiers in Microbiology, 2018)
We report extremely low-light-adapted anoxygenic photosynthesis in a thick microbial mat in Magical Blue Hole, Abaco Island, The Bahamas. Sulfur cycling was reduced by iron oxides and organic carbon limitation. The mat grows below the halocline/oxycline at 30 m depth on the walls of the flooded sinkhole. In situ irradiance at the mat surface on a sunny December day was between 0.021 and 0.084 μmol photons m-2 s-1, and UV light (<400 nm) was the most abundant part of the spectrum followed by green wavelengths (475–530 nm). We measured a light-dependent carbon uptake rate of 14.5 nmol C cm-2 d-1. A 16S rRNA clone library of the green surface mat layer was dominated (74%) by a cluster (>97% sequence identity) of clones affiliated with Prosthecochloris, a genus within the green sulfur bacteria (GSB), which are obligate anoxygenic phototrophs. Typical photopigments of brown-colored GSB, bacteriochlorophyll e and (β-)isorenieratene, were abundant in mat samples and their absorption properties are well-adapted to harvest light in the available green and possibly even UV-A spectra. Sulfide from the water column (3–6 μmol L-1) was the main source of sulfide to the mat as sulfate reduction rates in the mats were very low (undetectable-99.2 nmol cm-3 d-1). The anoxic water column was oligotrophic and low in dissolved organic carbon (175–228 μmol L-1). High concentrations of pyrite (FeS2; 1–47 μmol cm-3) together with low microbial process rates (sulfate reduction, CO2 fixation) indicate that the mats function as net sulfide sinks mainly by abiotic processes. We suggest that abundant Fe(III) (4.3–22.2 μmol cm-3) is the major source of oxidizing power in the mat, and that abiotic Fe-S-reactions play the main role in pyrite formation. Limitation of sulfate reduction by low organic carbon availability along with the presence of abundant sulfide-scavenging iron oxides considerably slowed down sulfur cycling in these mats.